Why Do I Have to Learn this Stuff? Using AI to Assist Secondary Teachers in Teaching Future-Ready Practical Life Skills with any Social Studies Lesson - Greg Levitt,; Steven Grubaugh, (Technium Social Sciences Journal, 2024)
The integration of Artificial Intelligence (AI) in secondary social studies education is revolutionizing the way students prepare for their future. By embedding 'Future Ready Practical Life Skills' into the curriculum, educators can effectively address the question, "Why do I have to learn this?" and equip students with the necessary competencies for success in college, careers, and active civic life in an AI-dominant future. This article explores how AI nurtures critical thinking, digital literacy, adaptability, ethical reasoning, and civic engagement -- skills that are crucial not only for navigating advanced technologies but also for dealing with daily life situations. By creating a dynamic and personalized learning experience, AI-driven social studies education fosters vital competencies for students to confidently face challenges and make informed decisions in their personal and civic lives. This paradigm shift in teaching and learning sets students up for success in an AI-shaped future while empowering them to navigate the complexities of daily life.